Badenian rhodolith in Kozjansko (E Slovenia) - Aničić, Bogoljub; Ogorelec, Bojan (Geologija, 1994)
Rhodolith beds are the basal transgressive unit of the several hundred metres thick Badenian succession, and are a peculiarity of the Kozjansko area. Rhodoids are mainly spherical having up to 15 cm in diameter. They are built of Lithothamnium corallinacean algae with crusty and branching texture, frequently intergrown with bryozoans. The rhodoid nuclei commonly consist of pebbles of Palaeozoic clastic rocks (quartz, phyllites), Triassic carbonates and Oligocene tuffs. The rhodolith occasionally passes into a rhodolithic conglomerate. Sparsely rhodoids of somewhat smaller dimensions also occur in lithothamnium limestone (biocalcarenite). Rhodolith was formed in nearshore, well agitated areas of the Tertiary Kozjansko basin.